PENGARUH PAPARAN EXTREMELY LOW FREQUENCY MAGNETIC FIELD TERHADAP pH EDAMAME - Emi Ariyani; Sudarti Sudarti; Sri Handono Budi Prastowo (JURNAL PEMBELAJARAN FISIKA, 2019)
Extremely low frequency magnetic field (ELF) is a part of the electromagnetic spectrum with range of 0-300 Hz of frequency and non ionizing characteristics of radiation. Nowadays, ELF magnetic fields are widely used in various fields, for example in the fields of medicine, agriculture, and food. In the field of food, ELF magnetic fields can be used as a preservation of materials that are easily damaged (decayed), one of which is agricultural product. Edamame is a top commodity in Jember that tends to be unresistant to damage during storage, especially to decomposing if stored at room temperature. This study aims to determine the effect of ELF magnetic field exposure on the value of edamame pH on day 4, day 7, and day 10 after harvest. This study used 9 samples each for the control and experimental groups. The experimental group was given exposure to ELF magnetic fields with an intensity of 1000 µT for 60 minutes. The results showed that exposure to ELF magnetic fields affected the pH of edamame. The pH value in the control group was lower than the experimental group, as indicated by the pH value of the control group during the measurement decreased to 5,93, while the edamame pH in the experimental group was still above 6 Key word: Edamame, ELF magnetic field, pH